Grisel’s Syndrome: A Rare Complication following Adenotonsillectomy - Abdulkadir Bucak; Sahin Ulu; Abdullah Aycicek; Emre Kacar; Murat Cem Miman (Case Reports in Otolaryngology)
Grisel’s syndrome is a nontraumatic atlantoaxial subluxation which is usually secondary of an infection or an inflammation at the head and neck region. It can be observed after surgery of head and neck region. Etiopathogenesis has not been clearly described yet, but increased looseness of paraspinal ligament is thought to be responsible. Patients typically present with painful torticollis. Diagnosis of Grisel’s syndrome is largely based on suspicion of the patient who has recently underwent surgery or history of infection in head and neck region. Physical examination and imaging techniques assist in diagnosis. Therefore, clinicians should be aware of acute nontraumatic torticollis after recently applied the head and neck surgery or undergone upper respiratory tract infection. In this paper, a case of an eight-year-old male patient who had Grisel’s syndrome after adenotonsillectomy is discussed with review of the literature.